2018
DOI: 10.1186/s12977-018-0389-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the integrase–transportin-SR2 interaction block HIV nuclear import

Abstract: BackgroundCombination antiretroviral therapy efficiently suppresses HIV replication in infected patients, transforming HIV/AIDS into a chronic disease. Viral resistance does develop however, especially under suboptimal treatment conditions such as poor adherence. As a consequence, continued exploration of novel targets is paramount to identify novel antivirals that do not suffer from cross-resistance with existing drugs. One new promising class of targets are HIV protein–cofactor interactions. Transportin-SR2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Of note, nuclear transport has not been widely studied as a potential target to HIV-1 infection and only recently new hits impeding TNPO3-IN interactions blocking HIV-1 nuclear transport have been described [8]. Besides this role in HIV-1 infection, TNPO3 is also linked to a rare muscular dystrophy termed LGMD1F.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, nuclear transport has not been widely studied as a potential target to HIV-1 infection and only recently new hits impeding TNPO3-IN interactions blocking HIV-1 nuclear transport have been described [8]. Besides this role in HIV-1 infection, TNPO3 is also linked to a rare muscular dystrophy termed LGMD1F.…”
Section: Discussionmentioning
confidence: 99%
“…These PICs consist of viral cDNA and other HIV-1 components like integrase (IN), matrix, nucleocapsid, CA and viral protein R (Vpr), as well as various host proteins, such as the high mobility group protein B1 (HMGB1), barrier to autointegration factor 1 (BAF1), lamina-associated polypeptide 2α (LAP2α) and lens-epithelium derived growth factor (LEDGF/p75) [37]. Several cellular import factors, including importin-7, importin-α3 and Transportin 3 (TNPO3, also called TRN-SR2) have also been involved in HIV-1 nuclear import [8]. Apart from its implication in nuclear import of the viral PIC, it has been confirmed that N-terminal end of TNPO3 protein act as a direct binding partner of HIV-1 IN [9].…”
Section: Introductionmentioning
confidence: 99%
“…IN has been proposed to play additional roles in the HIV-1 lifecycle, including virus particle uncoating after cell entry (246) and PIC nuclear import (247,248 (268) or KPNA2/KPNB1 (269) in vitro displayed comparatively weak antiviral activities of less than 50% inhibition at 100 M and 50% inhibition at ϳ50 -100 M, respectively. To establish IN-KPN interactions as bona fide antiviral targets, it will be important to show that resistance to compounds with 10 -100-fold greater potencies maps to the IN region of HIV-1 pol.…”
Section: Other In Functionalitiesmentioning
confidence: 99%
“…Although HIV-1 infection is significantly reduced via TNPO3 depletion ( 19 , 83 , 90 , 93 , 94 ), this appears to be an indirect consequence of restriction of virus infection due to enhanced cytoplasmic CPSF6 accumulation ( 59 , 92 , 95–97 ). Comparatively weak, ∼0.1 mM, small molecule inhibitors of IN-TNPO3 ( 98 ) and IN-KPNA2/KPNB1 ( 99 ) interactions have been reported. Inhibitors with minimally 10-fold increases in potency together with the selection of drug resistance that maps to IN should be accomplished to convincingly demonstrate a pharmacological role for IN in HIV-1 PIC nuclear import.…”
Section: Introductionmentioning
confidence: 99%